A Changing Climate for Knowledge Generation in Agriculture: Lessons to Institutionalize Science-Policy Engagement - Dinesh, Dhanush; Hegger, Dries L. T.; Vervoort, Joost M.; Driessen, Peter P. J. (Frontiers in Climate, 2021)
Effective science-policy engagement efforts are crucial to accelerate climate action. Such efforts should be underpinned by high-quality knowledge generation that enhances salience, credibility and legitimacy of research results. This is particularly important for the agricultural sector. Agriculture has been identified as a priority for climate action. The sector also constitutes well-established institutions set up to help achieve food and nutrition security. Institutionalizing high quality knowledge generation for climate change adaptation within these institutions presents a major opportunity to catalyze climate action within the sector. To contribute to insights about this institutionalization, we draw on and develop Cash et al.'s 2002 success conditions for enhancing salience, credibility and legitimacy: (1) increased accountability, (2) use of boundary objects, (3) participation across the boundary, (4) mediation and a selectively permeable boundary, (5) translation, and (6) coordination and complementary expertise. We examine how these success conditions apply in a major global case of agricultural research for development under climate change: the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). We explore these success conditions in the wider context of CGIAR reform and response to climate change as the international system for Agricultural Research for Development (AR4D). Our results specify and confirm the practical relevance of the six success conditions for institutional design and reform, but also point to the need to complement these with two inductively-derived success conditions: effective leadership and presence of incentives. To institutionalize these success conditions among AR4D institutions, there is an urgent need to create a conducive environment that enables the development of context-specific science-policy engagement strategies, along with leadership development and efforts to break traditional disciplinary silos which constrain user-oriented knowledge production.